2014
DOI: 10.1155/2014/769012
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength Analysis of Starch Based Biodegradable Composite Using Areca Frond Fibre Reinforcement

Abstract: Natural fibres and biodegradable matrices are being considered nowadays as substitutes to synthetic fibre reinforced polymer composites mainly in sectors where high load carrying capacity and high strength are not prerequisites. Present study utilizes biodegradable matrix composite prepared by varying the weight of the base material (95-170 g), binder (5-10 g), and plasticizer (5-20 g) with treated areca frond fibres as reinforcement. Contents are transferred to a pneumatic press, compacted, and subjected to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Steam oven cured samples were 112%, 54%, and 22% stronger in bending than sunlight cured, OTG oven cured, and hot air oven cured laminates. Flexural strength results of steam cured laminates show an improvement when compared to composites cured in similar conditions using sodium carbonate treated fibres [11].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 86%
See 1 more Smart Citation
“…Steam oven cured samples were 112%, 54%, and 22% stronger in bending than sunlight cured, OTG oven cured, and hot air oven cured laminates. Flexural strength results of steam cured laminates show an improvement when compared to composites cured in similar conditions using sodium carbonate treated fibres [11].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 86%
“…The authors observed an increase in tensile strength with increase in starch content. Heckadka et al [11] used Taguchi technique to study the flexural strength of the areca frond fibres reinforced with starch, methyl cellulose, resorcinol, and glycerol based matrix material using hand lay-up/compression moulding technique. The authors reported that glycerol as plasticizer had maximum effect on the flexural strength of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Glenn [15] demonstrated the use of wheat starch, corn starcch and potato starch to prepare foam by compression/ explosion processing which has potential to replace the single use foam packaging material. Srinivas Shenoy Heckada [14] used the corn starch with water and vinegar as biodegradable matrix with Areca Frond Fibre to produce completely biodegradable composite Hand Layup and hot pressing are the most popular methods utilized for the production of biodegradable composite as they are cost competitive and quite simple. Hamdy Ibrahim et.…”
Section: Introductionmentioning
confidence: 99%
“…Hamdy Ibrahim et. al [10] employed hot pressing to prepare starch based biodegradable composite reinforced with date palm and flax fibers whereas Srinivas Shenoy et al [14] used hand layup process followed by hot pressing to manufacture starch based biodegradable composite.…”
Section: Introductionmentioning
confidence: 99%